Effect of void-carbon on blue-shifted luminescence in TADF molecules by theoretical simulations - Zhang, Boyuan; Xu, Haoyang; Xia, Yumin; Wen, Jin; Zhu, Meifang (Frontiers in Chemistry, 2023)
Thermally activated delayed fluorescence (TADF) molecules have a theoretical 100% photoluminescence quantum yield in comparison with traditional fluorescent materials, leading to broad application in organic light-emitting diode (OLED). However, the application of TADF molecules with conjugated donor-acceptor structures in blue OLED remains a challenge due to their generally narrow energy gap between frontier molecular orbitals. Recently, a strategy has been approved in the improvement of the performance in TADF, in which void-carbon atoms between donor and acceptor fragments (donor-void-acceptor (D-v-A)) could regulate blue light emission. In this study, we first select three reported isomers followed by two proposed D-v-A TADF isomers to verify the feasibility of the void-carbon strategy through evaluation of the electronic structures in the excited state and photophysical properties. We further proposed a series of TADF molecules by replacing different donor and acceptor fragments to assess the applicability of the void-carbon strategy from the aspect of simulations in electronic structures, different properties of donor and acceptor fragments, photophysical properties, and analysis in the molecular conjugation. The results indicate that void-carbon strategy has conditional feasibility and applicability. Donor-acceptor molecular properties could be tuned through void-carbon strategy on aromatic acceptor fragments during the selection of promising candidates of TADF molecules. However, the void-carbon strategy does not work for the molecules with antiaromatic acceptor fragments, where the steric hindrance of the molecules plays a dominant role. Our work provides insightful guidance for the design of the blue-emission TADF molecules.